Increased levels of plasma interleukin-6 soluble receptor in patients with essential thrombocythemia - Marta, Rosana Fernanda (2004)
Background and Objectives. The pathogenesis of essential thrombocythemia (ET), a disease characterized by megakaryocyte hyperplasia and persistent thrombocytosis, is not completely clarified. Interleukin-6 (IL-6), one of the cytokines related to megakaryocytic development, exerts its effect through binding to a cell surface receptor, IL-6Ra, and a signal transducing unit, gp130. Interestingly, the soluble form of the IL-6Ra, IL-6sR, is an agonist for IL-6 activity. In order to evaluate the possible participation of IL-6sR in ET we measured its levels in plasma, platelets and in the supernatant of a mononuclear cell culture. We also evaluated IL-6R on leukocyte membrane and IL-6R/IL-6sR mRNA expression in mononuclear cells. Design and Methods. Fifty-five patients with ET were evaluated. IL-6sR and IL-6 were measured by an ELISA technique. Mononuclear cells were cultured for 48 hr and IL-6sR released into the supernatant was measured. IL-6R on leukocyte surfaces was evaluated by flow cytometry. IL-6R and IL-6sR mRNA levels were assessed by semi-quantitative reverse transcription polymerase chain reaction. Results. Plasma IL-6sR levels were increased while intraplatelet levels were low in untreated ET patients. Plasma levels decreased during treatment. Non-stimulated mononuclear cells from ET patients released greater amounts of IL-6sR than did cells from normal controls in 48-hour culture. No abnormality was found in IL-6R or IL-6sR mRNA expression by mononuclear ET cells. IL-6R on leukocyte surfaces was normal. Interpretations and Conclusions. Increased plasma IL-6sR levels might have a role in the abnormal megakaryocytic proliferation seen in ET patients, while platelets and mononuclear cells could be the source of the above-mentioned high levels of plasma IL6sR.